CD20 staining assists decision on adiuvant immunotherapy in B cell lymphoma - Klimczak, Aleksandra; Lange, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2002)
B cell non-Hodgkin lymphoma (NHL) originates from cells at different levels of differentiation residing in some areas of the lymphoid organs. Consequently lymphoma cells harbour appropriate cluster of differentiation antigens. B-cell lymphoma may be positive for CD20 antigens. Morphological description of lymphoma in addition to standard pathological picture (follicular or diffuse) may involve more detailed phenotyping characteristics. A panel of monoclonal antibodies was used including CD20 antigen. Also to describe biological property of lymphoma staining for the presence of Ki67 and DR antigens was done and presented. Having all these information a pattern of immunopathomorphological features was described in lymphomas characterised by routine pathomorphology as: diffuse large B-cell lymphoma, follicular centre lymphoma, extranodal marginal zone B-cell lymphoma, nodal marginal zone B-cell lymphoma, primary mediastinal large B-cell lymphoma. In general follicular lymphomas had lower and diffuse lymphomas higher proportion of Ki67 cells. However in these two morphological variants of lymphoma were cases with higher percentage of Ki67+ cells than expected by their follicular morphology and in diffuse lymphomas they were cases with lower proportion of Ki67+ cells than in a majority of situations. In diffuse B-cell lymphomas these composed of large cells had a higher proportion of Ki67+ than those with small cells. MALT lymphomas could be also differentiated on the basis of Ki67+. In one out of 5 cases the proportion of Ki67+ cells was lower than in other cases. All follicular and MALT lymphomas were CD20+. Ki67 and CD20 staining results help in tailoring adequate therapy. Lymphomas with a high proportion of Ki67+ cells are candidates for more aggressive treatment and those with CD20 independent on their follicular or diffuse morphology may benefit from treatment including anti-CD20 antibody. Recently a monoclonal antibody specific for CD20 was clinically introduced.